The Influence Of Village Officials, Community Participation, And Educational Background Of Village Heads On Accountability Of Village Fund Management With Leadership Style As A Variable Of Moderation - Jayadi Jayadi; Setiawati Setiawati; Sutarti Sutarti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Village funds are allocations of money to support government activities, development projects, community activities, and community empowerment. Accountability is the obligation to report and be responsible for the success or failure of the organization's mission in achieving previously set results, through periodic accountability media. Accountability in village fund management is the obligation to report and be responsible for the village funds managed for the benefit of village development and the welfare of the village community. The purpose of this research is to examine the influence of village apparatus, community participation, and the educational background of village heads on the accountability of village fund management with leadership style as a moderating variable. This research is a quantitative study with a population of all village officials in Electoral District 6, Bogor Regency, totaling 671 people. The research sample consisted of 87 respondents determined using the Slovin formula with a 10% margin of error and with the sampling technique using purposive sampling. Data analysis using Structural Equation Modelling (SEM) with a Partial Least Square approach (PLS). The research results indicate that the knowledge, skills, and experience of village officials have a negative and significant impact on the accountability of village fund management, possibly due to a lack of skills or potential fraud. On the contrary, community participation has a positive impact, indicating that public involvement increases social pressure and oversight of the village government. The educational background of the village head also has a positive impact, strengthening accountability through a better understanding of financial management. However, when community participation is moderated by leadership style, the impact becomes negative, highlighting the importance of effective leadership. A good leadership style reinforces the positive impact of village head education. Keywords: Accountability; Village Fund Management; Village Apparatus; Community Participation; Educational background; Leadership Style